Genome-wide association study identifies inversion in the CTRB1-CTRB2 locus to modify risk for alcoholic and non-alcoholic chronic pancreatitis - Rosendahl, Jonas; Kirsten, Holger; Bugert, Peter; Frank, Josef; Kiefer, Falk; Mann, Karl; Mueller, Sebastian; Rietschel, Marcella; Schneider, Alexander (Gut, 2018)
Alcohol-related pancreatitis is associated with a disproportionately large number of hospitalisations among GI disorders. Despite its clinical importance, genetic susceptibility to alcoholic chronic pancreatitis (CP) is poorly characterised. To identify risk genes for alcoholic CP and to evaluate their relevance in non-alcoholic CP, we performed a genome-wide association study and functional characterisation of a new pancreatitis locus.